Integrating Classical Islamic Philosophical Thought and Modern Environmental Ethics: Toward a Sharia-Rooted Eco-Theology for Global Sustainability - Rawuh Yuda Yuwana; Chairul Hakim (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
This study explores the intersection of classical Islamic philosophical thought and modern environmental ethics to propose a Sharia-based eco-theology model for addressing global sustainability challenges. It investigates key Islamic environmental principles, such as khalifah (stewardship), amanah (trustworthiness), and mizan (balance), which emphasize humanity’s responsibility to protect and preserve the environment. These values, derived from Islamic teachings, offer a moral and spiritual framework for ecological stewardship, aligning closely with contemporary concerns like sustainability, biodiversity preservation, and climate change mitigation. The research integrates these Islamic principles with modern ecological ethics, including ecocentrism, deep ecology, and environmental justice, to construct a holistic eco-theological model. Through this framework, the study emphasizes the importance of balancing ecological, economic, and social factors to promote environmental justice. The findings suggest that Islamic eco-theology can play a significant role in fostering environmental responsibility within Muslim communities and beyond, contributing to global sustainability efforts. Practical applications of these principles are seen in educational initiatives, such as the incorporation of eco-theology into curricula at Islamic institutions, and in community-based environmental projects. The research also highlights the challenges and limitations of traditional interpretations of Islamic environmental ethics, suggesting the need for progressive and adaptive approaches in addressing modern environmental issues. Future research directions include exploring the integration of this eco-theology in policy-making, Islamic education, and cross-cultural applications, ensuring its relevance to diverse communities facing environmental challenges.